Facile synthesis of carbon nanofibers/MnO2 nanosheets as high-performance electrodes for asymmetric supercapacitors. (20th August 2016) - Ning, Peigong; Duan, Xiaochuan; Ju, Xiaokang; Lin, Xiaoping; Tong, Xiaobin; Pan, Xi; Wang, Taihong; Li, Qiuhong
Abstract: We reported the facile synthesis of hollow carbon nanofibers/MnO2 (CNFs/MnO2 ) composites for high performance supercapacitor electrodes. The nanocomposites were prepared via electrospinning of carbon nanofibers/MnOx and subsequent hydrothermal coating of MnO2 nanosheets on the surface. The unique hollow structure and numerous MnO2 nanosheets increased the contact area between the electrodes and electrolyte so that the CNFs/MnO2 electrode exhibited higher electrochemical performance than the CNFs/MnOx composites. The CNFs/MnO2 composites displayed a specific capacitance of 151.1 F/g at 1 A/g, and 90% of the initial specific capacitance was maintained after 8000 cycles. An asymmetric supercapacitor was assembled with the CNFs/MnO2 composites and the active carbon. The asymmetric supercapacitor exhibited a high performance in 1 M Na2 SO4 aqueous solution with a working potential window ranging from 0 to 1.8 V. Furthermore, the asymmetric supercapacitor possessed a cycling stability with 93.5% capacitance retained after 1500 cycles at 1 A/g.